PENERAPAN PENDEKATAN KONSTRUKTIVIS DALAM UPAYA PENINGKATAN PEMAHAMAN KONSEP LINGKARAN PADA SISWA KELAS VIII-A SMP NEGERI 1 LANGGUDU KABUPATEN BIMA - Nurrahmah Nurrahmah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2014)
Teachers still use many conventional methods. Finally, the students' participation is inactive to find concepts and determine their own solutions. Therefore, a constructivist approach to the material of the circle was applied to the students of SMP Negeri 1 Langgudu Kabupaten Bima. The constructivist approach is one of the learning approaches that enable students. The purpose of the research is to improve the understanding of student learning concepts and activities through the application of constructivist approach. The study was conducted with classroom action research procedures. Implemented two cycles that include: the planning, implementation, observation, and reflection. The subjects of this study are students of class VIII - A semester II junior high school consisting of 33 students. The research instrument used is 1) Test the learning outcomes given at the end of the learning cycle. 2) The observation sheet, used to obtain a direct description of the learning activities of mathematics through a constructivist approach. The data analyzed is mastery learning. The indicators are the increase in the average score of student learning outcomes, as well as student learning activities in each cycle. The results showed an increase in the average score of student learning outcomes in the first cycle is 58.97 with 'percentage mastery' 34.38%. In the second cycle, the average score of student learning outcomes of 84.36 with the percentage of '90.9% completeness. Student learning activities in the first cycle with an average score of 3.73 (active category), on the second cycle average score of 4.22 (active category). This value has been in accordance with research indicators that is an increase in the average score of student learning outcomes. It can be concluded that constructivist learning has increased the understanding of the concept of circle in students